PENENTUAN ZONASI DAERAH RAWAN BENCANA LONGSOR STUDI KASUS DI KECAMATAN TUMPANG, KABUPATEN MALANG - Mohammad Reza; Ghestiar Kharisma Kusumo; Mita Nur Bulan Sari; Alisya Fahza Nur Rahmah; Tasya Almira Syah Putri; Yohanes Kurnia Natalino; Muhammad Ilham (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2020)
Tumpang Subdistrict is one of the sub-districts in Malang Regency which has many steep slopes especially in the east of Tumpang Subdistrict, this area has a high potential for natural disasters, one of which disasters is landslides, so it needs to be repaired. Landslides by tracing the areas that caused landslides in order to minimize losses caused. The purpose of this study is to know the cause and distribution areas which has high potential of landslides. This research method is scoring and weighting, and overlapping with physical digital basic map Tumpang to get areas that use landslides, which are processed using ArcGis 10.2 software. The results of this study are Landslide Prone Maps which are maps that describe areas with the level of landslide vulnerability assessment in the study area. With this result, then it becomes a reference in landslide disaster mitigation to assist the government in diverting landslide disasters in the area